Abscess or tumour? Lumbar spinal abscess mimicking a filum terminale tumour. (30th May 2012) - Sajjad, Jahangir; Kaliaperumal, Chandrasekaran; O'Sullivan, Michael
Abstract : A 62-year-old woman presented with a 4-month history of central lower backache and a 2-week history of progressive bilateral leg weakness. She also complained of numbness on her left thigh and gluteal region, associated with urinary hesitancy and constipation. On examination, she had bilateral partial foot drop, absent knee and ankle reflexes and a negative Babinski's reflex and associated hyperaesthesia in L3 distribution bilaterally with decreased anal tone. Laboratory results revealed normal inflammatory markers. MRI scan demonstrated a large uniformly enhancing lesion in the filum terminale suggestive of a lumbar spinal tumour. An emergency spinal laminectomy from L3 to S2 was performed. Per operatively, the duramater was thickened and hyperaemic. The histopathology report suggested inflammation with no evidence of malignancy. Tissue specimen of cultured Staphylococcus aureus was sensitive to flucloxacillin. A final diagnosis of lumbar spinal abscess was made and subsequent antibiotic treatment led to good clinical recovery.